Changes in profiles of classes and of individual polyphenols in leaves of Spiraea chamaedryfolia and Spiraea media along an altitudinal gradient - Boyarskikh, Irina G.; Artemov, Igor A.; Kuznetsov, Alexander A.; Kostikova, Vera A. (Plants)
Plants in high-altitude habitats are exposed to severe environmental stressors, including extreme temperatures and irradiation, which can have wide-ranging effects on changes of secondarymetabolite profiles in higher plants. Altitude-related variation of levels of polyphenols in organs of medicinal and food plant species has not yet been investigated sufficiently. This study was focused on variation in quantitative profiles of classes and of individual biologically active phenolic compounds in leaf extracts of resource species Spiraea chamaedryfolia and Spiraea media from the family Rosaceae in coenopopulations of the Altai Mountains, along an altitudinal gradient. High-performance liquid chromatography revealed 22 polyphenolic compounds in the extracts of S. media leaves, with the main polyphenolic compounds being flavonols. Sixteen compounds were found in S. chamaedryfolia leaf extracts, and the major ones were flavonols and a flavanone. Opposite responses to changes in the altitude-associated growth conditions were documented for levels of some individual polyphenolic compounds. With an increase in altitude, concentrations of chlorogenic acid and of flavanone in the extracts of S. chamaedryfolia leaves significantly increased, while concentrations of cinnamic acid, astragalin, and kaempferol diminished. A statistically significant positive correlation between the altitude of plant habitats and total levels of polyphenols and phenolcarboxylic acids was detected. In leaf extracts from S. media, an altitude increase was significantly positively correlated with astragalin, avicularin, and cinnamic acid levels and negatively correlated with hyperoside concentration.